Duality of roles: understanding the work performance of teaching mothers on modular distance learning in the first Districtof City Division of Santa Rosa, Laguna - Delgado, Genell A. (Technium Social Sciences Journal, 2023)
Teaching is hard to perform specially during this trying time of the COVID 19 pandemic. Much more if the teachers themselves as performing dual roles as both teacher and mothers. This qualitative phenomenological study determined how teachers who are also mothers hurdle their dual roles and the factors that affect performance as a mother and teacher. Fifteen (15) purposely selected participants comprised the sample for this study. The participants were selected along the following inclusion criteria namely, an elementary school teachers in Santa Rosa Laguna, mothers with or without husbands or partners, have children of school-age and also attending home-schooling through virtual learning and other alternative learning modes, have expressed difficulties in coping with stressors in performing roles due to several factors of economic and psychosocial in nature and with teaching experience of not less than three (3) years; and under the implementation of modular distance learning. From the interpreted meanings nine (9) themes emerged as follows: (1) The Need to be Creative and Innovative; (2) Positive and Negative Sides of Technology; (3) Adapting to new Emerged Teaching Strategies is not easy; (4) Own Children need not be Sacrifice; (5) Compliance with the School Requirements; (6) Economic Condition and Teacher-Mothers Challenges; (7) Performing Dual Roles is Stressful; (8) Balancing Role as Teachers and as Mothers; and (9) Teaching is more difficult to Perform. On the whole, the results of this study can serve as basis for finding alternative solutions to unburden the mothers in their situation; provision of support to teachers in maintaining their effective professional qualities; consideration in upgrading salary of teachers; creation of stress management program; enhancement of teacher’s self-worth; and improvement in teachers’ practice and time management.